Analyzing The Software Sector In Bahia Blanca (Argentina) Using The Structure-Behavior-Performance And Capabilities Approach - Diez, Jose Ignacio Manuel (2022)
From the emergence of the techno-economic paradigm of ICTs, numerous clusters of Software and Information Services (SIS) are consolidated in developed countries. In developing countries, and particularly in smaller cities, the growth of this sector constitutes a potential path of economic-productive diversification. The study aims to explore the origin and current performance of the SSI sector in the city of Bahía Blanca (Argentina). Empirical findings show that the local SSI presents an embryonic development, with a limited capacity for innovation and export, conditioning its role as a factor of economic growth.